2021
DOI: 10.33919/esnbu.21.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Expressing Lesser Relevance in Academic Conference Presentations

Abstract: While marking importance and relevance in academic discourse has been a widely researched topic, markers of lesser significance have so far been understudied. The article therefore focuses on some of the discoursal means of expressing lesser importance in conference presentations. The corpus of the study comprises recordings of 20 presentations in English at international linguistics conferences by speakers of various cultural and linguistic backgrounds. The methodology follows Deroey and Taverniers’s (2012) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The research involved preliminary screening, corpus retrieval, determination of pragmatic function, categorization, and comparative statistical analysis. Previous studies, such asYankova and Vassileva (2021), have indicated substantial variations in the usage frequency of lesser relevance markers across different cultural backgrounds. Building on these findings, this study delves deeper into the distinctions between science and engineering and humanities and social sciences disciplines to investigate whether variations exist in the use of these markers across different cultures and disciplines.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The research involved preliminary screening, corpus retrieval, determination of pragmatic function, categorization, and comparative statistical analysis. Previous studies, such asYankova and Vassileva (2021), have indicated substantial variations in the usage frequency of lesser relevance markers across different cultural backgrounds. Building on these findings, this study delves deeper into the distinctions between science and engineering and humanities and social sciences disciplines to investigate whether variations exist in the use of these markers across different cultures and disciplines.…”
mentioning
confidence: 94%
“…Previous research has highlighted significant variations in the usage frequency of lesser relevance markers across disciplines, with reduced usage potentially impacting readers' comprehension and evaluation of academic papers (Hyland, 1998(Hyland, , 2004(Hyland, , 2005Xiao, 2010). Furthermore, Wang and Sun (2018) found that factors such as speaker gender, discourse mode, and academic discipline influence the use of lesser relevance markers in academic spoken language, while Yankova and Vassileva (2021) observed that Bulgarian scholars tend to use lesser relevance markers less frequently compared to native English speakers, potentially attributable to cultural backgrounds. Hence, the study of lesser relevance marker distribution across disciplines and cultures is essential for understanding their pragmatic and discourse functions in diverse academic contexts and cultural settings.…”
Section: Introductionmentioning
confidence: 99%